2001
DOI: 10.1038/sj.onc.1204976
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and poly-ubiquitylation of the DEAD-box RNA helicase p68 in colorectal tumours

Abstract: The DEAD box RNA helicase, p68, is upregulated in exponentially growing cells and shows cell cycledependent changes in nuclear localization. Although some other DEAD box proteins have been implicated in cancer, there have been no reports of any link between p68 status and carcinogenesis. In the present study we have analysed specimens from 50 patients with colorectal adenocarcinomas, including cases in which an adenomatous polyp was also present, by immunohistochemistry and Western blotting. Our data indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
120
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 30 publications
5
120
0
Order By: Relevance
“…Their role in tumor growth has been reported previously for some members of this family. For instance, p68 (DDX5), p72 (DDX17), and Cancer Associated Antigen (CAGE) (DDX53) have been implicated in promoting cell proliferation and survival in cancer cell lines from different tissue origins (18,(27)(28)(29)(30)(31). Members including Cancer Associated Antigen (CAGE) and HAGE (DDX43) were found to be highly expressed in different cancer tissues and cancer cell lines, suggesting their possible role in tumorigenesis (13,28,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Their role in tumor growth has been reported previously for some members of this family. For instance, p68 (DDX5), p72 (DDX17), and Cancer Associated Antigen (CAGE) (DDX53) have been implicated in promoting cell proliferation and survival in cancer cell lines from different tissue origins (18,(27)(28)(29)(30)(31). Members including Cancer Associated Antigen (CAGE) and HAGE (DDX43) were found to be highly expressed in different cancer tissues and cancer cell lines, suggesting their possible role in tumorigenesis (13,28,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several reports have indicated that the splicing and transcriptional activities of ddx5 and ddx17 can be modulated by different post-translational modifications that depend on cellular signaling pathways (Yang et al, 2006(Yang et al, , 2007Jacobs et al, 2007;Carter et al, 2010;Mooney et al, 2010a, b). In addition, several post-translational modifications of ddx5 or ddx17 have been shown to be altered in different cancers (Causevic et al, 2001;Yang et al, 2005). Therefore, different cellular signaling pathways activated in different cellular contexts may favor one of the molecular functions of ddx5 and ddx17, which could have different impact on cell behavior and tumor progression.…”
Section: Ip Flagmentioning
confidence: 99%
“…p68 interacts with a protein kinase A anchoring protein, AKAP95 (Akileswaran et al, 2001), and is a coactivator of the human estrogen receptor a in cooperation with an RNA coactivator (Endoh et al, 1999;Watanabe et al, 2001), pointing at a role for p68 in hormonally responsive transcription complexes. Furthermore, p68 has been recently implicated in tumor development, as p68 is overexpressed in colorectal tumors when compared to normal tissue samples (Causevic et al, 2001). Similarly, other DEAD box RNA helicases appear to be involved in tumor development.…”
mentioning
confidence: 99%
“…Accordingly, our results support the hitherto little-recognized notion that RNA helicases, in general, are important transcriptional regulators. As a corollary, dysregulation of transcription upon RNA helicase overexpression may contribute to the formation of various tumors, including colorectal ones where p68 RNA helicase has been found to be overexpressed (Causevic et al, 2001).…”
mentioning
confidence: 99%